Social media video clips as social commentary in Southern and East Africa: a case study of Admire Kuzhangaira, Rolland Lunga, Kansiime Anne and Pepukai Zvemari - Zinyanga, Learnmore (Midlands State University, 2020)
A lot has been done to show the socio-economic and political issues affecting the Southern and East African societies up to the present day through various forms of media. The aim of this study is interrogate the site of social media video clips as social commentary in Southern Africa and East Africa and the main objectives is to identify the themes as well as interrogate how the themes were effectively interrogated the other objectives was to identify the techniques used to convey the message as well as to assess the effectiveness of the techniques. From the findings of this study, it has been also noted that there are some similarities in terms of themes that has been put forth by the comedians for instance Kansiime, Rolland and Admire have looked on the issues of corruption and Gender equality. There are also some differences that have been taken not of for instance, those of themes, Rolland and Admire are more of political whereas Kansiime and Pepukai looked on social and economic issues.There is also issue of Gender, Kansiime is a woman, Rolland, Admire and Pepukai are men that alone influence their way of seeing things within the society. This study has roped in the audience receptionist analysis theory of Stuart Hall (1997) to analyse the content, the theory states that media content is encoded by the maker and these texts will be full of ideas and messages, its strength is that it allows the audience to decoded the meaning of the content offered, however, it also have its weaknesses for instance, audiences might generalise the meaning of the critical issues. Even though the analysis has been carried out, the room for further study is obtainable, one can carry out a study of social media as social commentary or social protests in the entire region or the entire continent paying particular attention to comedy and drama.